Corticosteroids alter CGRP and melatonin release in cluster headache episodes. (April 2015) - Neeb, Lars; Anders, Linn; Euskirchen, Philipp; Hoffmann, Jan; Israel, Heike; Reuter, Uwe
Background: Calcitonin gene-related peptide (CGRP) is a marker of trigeminal activation in acute cluster headache (CH). Melatonin production is altered in CH patients and may reflect hypothalamic dysfunction. We assessed the effects of short-term CH prevention with corticosteroids on CGRP and melatonin release in a prospective observational cohort study hypothesizing that corticosteroids influence the interictal activity of both systems indicated by the change of these biomarkers. Methods: Episodic CH subjects ( n = 9) in the bout and controls with multiple sclerosis ( n = 6) received 1000 mg/d methylprednisolone (MPD) i.v. for three days followed by oral tapering with prednisone. We determined CGRP plasma levels in external jugular vein blood outside an attack and 6-sulfatoxymelatonin (aMT6s) – the stable metabolite of melatonin – in 12-hour day- and nighttime urine collection prior to and several times after MPD therapy and again when CH subjects were outside the bout in complete remission. CH patients recorded the frequency of attacks. Results: In parallel to the reduction of headache frequency, administration of corticosteroids resulted in significantly decreased CGRP plasma levels and increased nocturnal aMT6s urine excretion in CH subjects. No significant changes were observed in controls. Conclusion: Corticosteroids alter CGRP plasma and aMT6s urine levels in a cluster bout. These changes may indicate an effect of corticosteroids on trigeminal activation and hypothalamic dysfunction.